(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In article signiﬁ cance of freedom category in philosophy and science demarcation is analyzed. If the scientiﬁ c knowledge is directed on reﬂ ection existing and creation of integrated system of knowledge of it as data, the philosophy is urged to develop and prove creatively valuable and world-view meanings as due, to reveal their logic, to comprehend tendencies of development and possible forms of their being manifestation. Such meanings as meanings of life of the person there can be a big variety, constituting spiritual heritage of mankind. It is connected with ontological freedom of the person as his initial essence and openness to creativity of spiritual meanings as the meanings of his being, a world outlook basis. The outlook is considered as the spiritual basis of human life deﬁ ning all spheres of creative activity of the person, including his knowledge. However the concept of freedom of philosophy was understood differently that deﬁ ned the philosophy status in relation to science. But method and way of scientiﬁ c cognition have metaphysical foundations. Logic of science as M.Heidegger and G.Markuse noted is historical. Keywords: philosophy, science, ontological freedom, neсessity, due, existing, alienation, reﬂ ection, creation, value sense, world outlook, comprehension, explanation.